Reflections on anthropology and political freedom in Ludwig Feuerbach (Cadernos de Filosofia Alemã: Crítica e Modernidade, 2021)
The article exposes Ludwig Feuerbach's anthropological thought in the dimension of politics, emphasizing that his critique of religion, beyond the reduction of the religious object to subjectivity, supports political contours in favor of men's selfdetermination. In this context, we reflect on the theme of freedom and the conditions for its effectivity. In articulation with the philosopher's ideas, we make a brief incursion into history evoking the criticism of José Carlos Mariátegui (1894-1930) regarding the process of political opening in Peru, analyzing the indigenous issue as marked by the difference between the unique way of life of these peoples facing the challenges posed by the republic, a dilemma whose assumptions we unveiled from Feuerbach onwards and which persists in the current political debate concerning the legitimacy of different forms of social and political organization.